Organizational Justice And Workplace Deviance: The Role Of Organizational Structure, Powerlessness, And Information Salience - McCardle, Jie Guo (2007)
The purpose of this study is to investigate both individual and structural factors in predicting workplace deviance. Deviant workplace behavior is a prevailing and costly phenomenon in organizations. It includes a wide range of negative acts conducted by employees to harm the organization and its members. In the first section, I conducted a comprehensive literature review. In the review, I first review the current state of research on the relationship between organizational justice and workplace deviance by presenting the various theoretical frameworks, as well as empirical findings. Next, I summarize existing research patterns and identify research challenges that must be overcome in order to advance our understanding of this topic. Finally, I offer future directions researchers should undertake in justice-deviance research. Specifically, I suggest the development of more comprehensive models that include potential moderators and mediators that may better explain how and why justice judgments can lead to deviant behaviors and when the negative effect is most damaging. In the second section, I developed a theoretical model that proposes the relationship between organizational justice, organizational structure (centralization and organicity), employee perceived powerlessness, information salience about each type of justice, and workplace deviance. In the third section, I tested the model and presented the findings. Results of HLM analysis show that (1) organizational justice, perceived powerlessness, and centralization exert direct effects on workplace deviance, (2) organicity exerts direct effects on justice information salience; (3) perceived powerlessness partially mediates the relationship between centralization and organizational deviance; (4) information salience of procedural justice strengthens the effects of procedural justice on interpersonal deviance. Conclusions are drawn from the theory and findings, highlighting implications for future workplace deviance and organizational behavior research